2017
DOI: 10.17159/1727-3781/2016/v19i0a1228
|View full text |Cite
|
Sign up to set email alerts
|

Realising the Child's Best Interests: Lessons from the Child Justice Act to Improve the South African Schools Act

Abstract: Although the contexts of school discipline and child justice differ considerably there are a number of contact points and points that overlap. Since the South African Schools Act 84 of 1996 came into operation in 1996, the Constitutional Court has made several pronouncements on the best-interests-of-the-child concept which are not reflected in the provisions regarding school discipline. The Child Justice Act 75 of 2008 came into operation in 2010. This Act provides valuable guidance on how to deal with transgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…I am just waiting for the police to come to my house for him. 31 While the Child Justice Act has the noble aim of ameliorating the impact of criminal justice processes on children, 32 the S v L M case illustrates how these protections are not always upheld once children are in the pipeline. 33 The High Court found that the CYCC custodial order was not a competent diversion option for a minor offence, 34 and that the Child Justice Act was variously ignored or misapplied by prosecutors and magistrates.…”
Section: S V L M: a Direct 'School-to-prison' Pathwaymentioning
confidence: 99%
“…I am just waiting for the police to come to my house for him. 31 While the Child Justice Act has the noble aim of ameliorating the impact of criminal justice processes on children, 32 the S v L M case illustrates how these protections are not always upheld once children are in the pipeline. 33 The High Court found that the CYCC custodial order was not a competent diversion option for a minor offence, 34 and that the Child Justice Act was variously ignored or misapplied by prosecutors and magistrates.…”
Section: S V L M: a Direct 'School-to-prison' Pathwaymentioning
confidence: 99%
“…Within the South African context, the best interests of a child has formed part of South African common law for many years (Bonthuys 2005:24;Malherbe 2008:267;Reyneke 2016:4;Sisilana 2016:15;Visser 2007:459). However, the inclusion of Section 28(2) in the Constitution has the best interests of the child becoming an enforceable constitutional right (Reyneke 2016) or principle (Bonthuys 2005:25). To contextualise Section 28(2), it is necessary to consider the legal background to the best interests principle, as well as the wording of this particular section of the Constitution.…”
Section: Best Interests Of the Childmentioning
confidence: 99%
“…Reyneke (2016) calls for the same child-centred approach in the interpretation of Section 28(2) of the Constitution by calling attention to the CC's interpretations of the said section and how these verdicts highlight the need to follow a child-centred approach when matters pertaining to children are considered. Based on various legal documents and the opinions of various academics, Reyneke (2016) is of the opinion that the best interests standard is not only applicable to the implementation of legislation relating to children, albeit individually or as a group, but also to actions, proceedings or decisions concerning children taken by an organ of the state, such as a public school. Walker in Stefkovich (2006:21) warns that one of the greatest obstacles in ensuring the best interests of children may be adult-centricity.…”
Section: Best Interests Of the Childmentioning
confidence: 99%
“…According to research, many South African educators find it challenging to administer discipline, especially after corporal punishment was banned (Reyneke, 2016). Makhasane and Chikoko (2016) assert that a number of incidents of learner disobedience have been documented in schools and have had a detrimental effect on instruction.…”
Section: Background To the Studymentioning
confidence: 99%